MOVES, INTENTIONS AND THE LANGUAGE OF FEEDBACK COMMENTARIES IN EDUCATION - Mirador, Josephine (Universitas Pendidikan Indonesia, 2014)
Abstract: This article discusses the results of an investigation into feedback commentaries provided by tutors to assignments of Masters in Education students in a pre-2002teaching and learning institution in the UK. The methodology adopted involved a qualitative discourse analysis of fifty feedback commentaries and made use of an inter-rating procedure involving three raters to identify tutor messages. The investigation revealed three groups of ‘moves’ (tutor messages) in feedback. Additionally, the article argues that tutor messages can find theoretical anchor in Heron’s categories of counselling interventions, and that such categories can explain tutor intentions in feedback provision. The research concludes that the use of facilitative ‘moves’ by tutors is a way for them to provide strong support to postgraduate students. Keywords: Written feedback, move analysis, tutor commentaries, feedback in higher education